The murine IRAK2 gene encodes four alternatively spliced isoforms, two of which are inhibitory - O'NEILL, LUKE ANTHONY JOHN (The American Society for Biochemistry and Molecular Biology, 2004)
The interleukin-1 receptor-associated kinases (IRAKs) are important downstream signaling components of Toll-like receptors (TLRs). To date, four mammalian IRAKs have been found, namely IRAK-1, IRAK-2, IRAK-4, and IRAK-M. Herein, we show a detailed analysis of the genomic region encompassing the murine Irak2 gene and the molecular cloning of four isoforms of Irak2 (designated Irak2a, Irak2b, Irak2c, and Irak2d) generated by alternative splicing at the 5?-end of the gene. This alternative splicing has direct effects on the expression of the N-terminal death domain and/or inter-domain. No evidence of similar alternative splicing was found for the human IRAK2 gene. When overexpressed, Irak2a and Irak2b potentiated NF-?B activation by lipopolysaccharide. Importantly, Irak2c and Irak2d were inhibitory. The promoter for Irak2c differed from that of the other Irak2 isoforms in that it contained putative NF-?B binding sites. Lipopolysaccharide induced the expression of Irak2c, indicating a possible negative feedback effect on the signaling pathway. Alternative splicing of the Irak2 gene in mice will therefore generate agonistic or antagonistic Irak2 isoforms, which is likely to have consequences for the regulation of TLR signaling. These observations identify another distinguishing feature between mice and humans in the TLR system that is likely to be due to differences in the selective pressure imposed by pathogens on each species during evolution.
PUBLISHED
Keywords: Biochemistry